دراسة دينامية مجتمعات نيماتودا التقرح Pratylenchus spp. في ريزوسفير نبات الفول السوداني خلال موسم النمو في بعض المحافظات السورية - خليل, حسن; أبو الفضل, تيسير; العربي, صبحية (Latakia University Journal -Biological Sciences Series, 2019)
درس تطور أعداد مجتمع نيماتودا التقرح Pratylenchus spp. في ريزوسفير نبات الفول السوداني في أربع محافظات في سورية (حمص، وحماة، وطرطوس، واللاذقية) خلال الموسمين 2009 و2010. فظهر اختلاف بين متوسطات الكثافة العددية الأولية Pi (Population initial) في جميع الحقول المدروسة، وسجل معدل التكاثر ارتباطاً سلبياً بمتوسط الكثافة العددية الأولية r = -0.38، وارتباطاً موجباً قوياً بمتوسط الكثافة العددية النهائية 97r = 0.، وكان متوسط الكثافة العددية لهذه النيماتودا غير متجانس في مناطق الدراسة، فقد بلغ متوسط الكثافة العددية الذروة في شهري تموز وآب للموسمين 2009 و2010 على التوالي، مسجلاً فرقاً معنوياً مع تاريخ أخذ العينات خلال الموسمين، وراوح ارتباط درجات الحرارة اليومية التراكمية DD5 بمتوسط الكثافة العددية بين الضعيف والمتوسط (r = -0.2، r = -o.6) على التوالي، باستثناء اللاذقية في الموسم 2009؛ فقد كان الارتباط موجباً قوياً (r = 0.85). The population dynamics of lesionnemstode (Pratylenchus spp.) in Peanut rhizospher were investigated in four Syrian governorates (Homs, Hama, Latakia and Tartaus). During the two growing seasons of 2009 and 2010. A difference between the means of initial population density (Pi) was noticed in all studded fields, a negative correlation was observed between reproduction rate and the mean of initial population density (r = -o.38), and a positive strong correlation with the final population density (r = 0.97). The mean of population density of this nematode was inhomogeneous in all studded regions, the top of population density was in July and August of the two growing seasons of 2009 and 2010, respectively. A significant difference with the date of sampling during the two seasons showed the correlation between accumulated daily temeparatures (DD5) and the mean of population density which ranged between weak and moderate (r = -0.2, r = -o.6) respectively. Except for Latakiagovernrate in 2009, in this season the correlation was positive and strong(r = 0.85).